The right of consumers in terms of section 66 of the Competition Act No. 89 of 1998 to commence claims for financial losses suffered as a result of cartel infringement - Van Heerden, C.M. (Corlia) (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.